Linking normative theory to media policy-making: A case study of Kenya. (1st September 2014) - Ugangu, Wilson; Fourie, Pieter
The Kenyan media landscape has transformed considerably in the period starting in the early part of the 1990s. This change is largely attributed to liberalization of the social economic and political context. This period of expansion has at the same time seen various efforts by the government and its agencies to control and regulate the media landscape. The electronic media sector has been the most affected, with laws being proposed and passed by parliament to enable greater control by government of the expanding communication sector. However, these efforts have always been met with opposition from owners of media institutions in the country, academics and civil society. It is against this backdrop of change and transformation that this article seeks to argue the role of normative media theory in shaping and guiding the policy debate in Kenya. This is done against the background of acknowledging the general flux that characterizes normative media theory in a postmodern, globalized and new media landscape such as Kenya's.